1998
DOI: 10.2307/3434231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of Lead Dust Associated with Primary Lead Smelting

Abstract: The research presented in this artide assessed geochemical factors relating to dust pr d during primary lead smelting. Bulk dust samples and size-selective airborne dust samples were collected from four ar of a pimary lead smelter and analyz by X-ray diaction and sequential .chemical exrtion. X-ray di on showed that the smelter dusts were composed primarily of sulfides, oxides, sulfates, and silicates of meta ores, with galena being the primary dust component. Sequenti extraction revealed the solubility of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The mass distributions of individual chemical species can be determined by analyzing the chemical composition of particles collected in each size range, as described in the next section. Spear et al (1998) utilized an Andersen cascade impactor to study Pb concentrations around a Pb smelter. Corriveau et al (2011) used a Proton Induced X-ray Emission Spectroscopy Cascade Impactor (PCI) sampler to assess As contamination from a mine-tailing site.…”
Section: Mining and Smelting Operations And Environmental Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The mass distributions of individual chemical species can be determined by analyzing the chemical composition of particles collected in each size range, as described in the next section. Spear et al (1998) utilized an Andersen cascade impactor to study Pb concentrations around a Pb smelter. Corriveau et al (2011) used a Proton Induced X-ray Emission Spectroscopy Cascade Impactor (PCI) sampler to assess As contamination from a mine-tailing site.…”
Section: Mining and Smelting Operations And Environmental Assessmentmentioning
confidence: 99%
“…X-ray diffraction has been used to examine the mineralogy of non-soluble materials in dust (Spear et al, 1998; Querol et al, 2000; Moreno et al, 2007). Moreno et al (2007) identified silica, kaolinite, alunite, jarosite, illite and iron oxides in PM 10 particles in the vicinity of an ore processing plant near a gold mine in Southeastern Spain.…”
Section: Mining and Smelting Operations And Environmental Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronadite is a Pb-containing manganese oxide which forms a tunnel structure into which the Pb is associated (Post and Bish 1989;Post 1999). Mattheddleite-like minerals have been identified as major components of blast and dross furnace dust samples from Pb smelting operations (Spear et al 1998), such that identification of mattheddleite in this system may reflect the result of mining activities. Bindheimite is a constituent of the primary Pb-Ag ores in the Coeur d'Alene Mining district with nearly pure masses several feet in diameter (Lawson and Meyer 1964).…”
Section: Mineral Identificationmentioning
confidence: 99%